Hochhausfassaden und akustische Stadtraumgestaltung. - Techen, Holger; Knaack, Ulrich; Krimm, Jochen (Springer-VDI-Verl., 2015)
Hochhausfassaden haben einen großen Anteil am akustischen Klima der Städte. Durch Mehrfachreflexionen an großflächigen Glasfassaden erhöht sich der wahrnehmbare Schallpegel im Stadtraum. Das Potenzial, über eine Veränderung der Reflexionswirkung der Fassaden auf den Lärmeintrag in den Stadtraum positiv gestaltend einzuwirken, bleibt weitestgehend ungenutzt. Auch Werkzeuge der Architektur genügen im Umgang mit Lärm im Stadtkontext nicht mehr den aktuellen Anforderungen. Ausgehend von einer Feldmessung wurden die akustischen Potenziale eines möglichen Eingriffs über die Fassade in das zugehörige Stadtumfeld ausgelotet. Basierend auf der Möglichkeit einer Einflussnahme über die Fassade wurden in den Maßstäben 1:2 und 1:50 Modelle entwickelt und mit skalierten Impulsmessungen untersucht. Diese Dokumentation des Reflexionsverhaltens zeigt auf, mit welchen architektonischen Eingriffen sich eine akustisch wirksame Fassade planen lässt.

With the growing of city centres in urban agglomerations the related acoustic space comes more under the influence of high-rise facades. Due manifold reflections of sonic waves on glass facades the measureable noise level in the related urban acoustic space is far beyond convenient levels. With modified building envelopes the transformation of a discomfort city space towards a more convenient space can be obtained. But the possibility of gaining control on the noise level of urban spaces with modified building envelopes is not introduced to the designers, architects and engineers practising. Furthermore it gets clear that architecture tools like the orientation of sleeping rooms to the silent face of a building are outdated in a city setup with up to five noise sources from differing directions. Based on a real on site measurement several acoustic interventions on a facade were evaluated. In a 1:2 and 1:50 scale facade models are measured in a scaled measurement setup to investigate the effects ofintroducing acoustically potent structures to facade designs. The impact of architectural interventions regarding the reflection properties is documented by the measurement results.
Holding control on acoustic urban spaces with modified high-rise facades.
Keywords: Umweltschutz; Lärm; Lärmbelastung; Schallpegel; Stadtraum; Gebäude; Bebauung; Hochhaus; Fassade; Akustik; Reflexion; Fassadengestaltung; Messtechnik